2003
DOI: 10.7773/cm.v29i42.199
|View full text |Cite
|
Sign up to set email alerts
|

Maternal care in the California sea lion at Los Islotes, Gulf of California, Mexico

Abstract: IntroducciónEn muchas especies de mamíferos el sistema de apareamiento es la poliginia, y la supervivencia de las crías depende exclusivamente de sus madres ya que el cuidado parental de los machos es escaso o nulo, por lo que las hembras deben buscar Resumen Se analizaron algunos componentes conductuales del cuidado materno en el lobo marino de California en una colonia pequeña del sur del Golfo de California, comparándolos entre un año de condiciones ambientales normales (1996) y uno con condiciones afectada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
(70 reference statements)
1
7
0
1
Order By: Relevance
“…The curve for suckling observed during the reproductive period (May-August) also agrees with previous observations at Los Islotes by García-Aguilar and Aurioles-Gamboa (2003b). The highest intensity of suckling was recorded during June, and values decreased progressively as the season advanced.…”
Section: Discussionsupporting
confidence: 80%
“…The curve for suckling observed during the reproductive period (May-August) also agrees with previous observations at Los Islotes by García-Aguilar and Aurioles-Gamboa (2003b). The highest intensity of suckling was recorded during June, and values decreased progressively as the season advanced.…”
Section: Discussionsupporting
confidence: 80%
“…Because some immediate behavioral responses were observed but a consistent number of animals were present throughout the experiment, it is likely that sea lions were alarmed but not sufficiently threatened by our disturbance to illicit abandonment of the site (Blumstein et al , 2003). Females invest significant energy in maternal care and may avoid unnecessary behavioral responses, such as movement, while the pups are relatively immobile (Garcia‐Aguilar & Aurioles‐Gamboa, 2003; Parker et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the density of animals in colonies, Matthiopoulos et al (2005) indicated that populations that slowly decrease in size or have low densities tend to show higher site fidelity and philopatry than populations with fast growth rates or high densities. In the present study, we did not have data on animal density for every site and every year, except for 2000, 2002, and 2003(Young and Gerber 2008, and we were thus unable to analyze the correlation between population density and the fine-scale site fidelity index for the whole study period. Nonetheless, analysis of those 3 years showed that site B had the highest density (0.20 ind•m -2 ), followed by site C (0.09 ind•m -2 ), and lastly site A (0.05 ind•m -2 ).…”
mentioning
confidence: 87%
“…Number of male and female pups that were branded during the mating seasons from 1980 to 1984 at the Los Islotes rookery, Gulf of California. The total number of pups born each year was estimated from counts performed on board and on land during the second week of July, when most births had occurred (García-Aguilar and Aurioles-Gamboa 2003). Tabla 1.…”
Section: Fine-scale Site Fidelity Indexmentioning
confidence: 99%
See 1 more Smart Citation